Why Are Social Workers in Wales the 'Happiest'? A Conundrum Explored. (24th December 2018) - Pithouse, A; Brookfield, C; Rees, A
Abstract: The Guardian newspaper's survey of social workers in the UK published in 2015 made the discovery that 'The happiest social workers are in Wales'. In exploring why this may be so, the authors undertook an in-depth national online survey in 2017 of all social workers in Wales registered as employed at that point. The survey sought information including broad demographic features, qualifications, employment histories, decision making and relationships with management. The workforce is mainly white and female, with few higher degree qualifications other than at qualifying levels. They believe their work is of sound quality and are clear about their aims and responsibilities. Our analysis suggests a workforce not discomfited by invasive management and work-processing systems, nor do respondents appear disempowered in matters of work decision making over which they claim much control. Most look forward to going to work. The data suggest a workforce that is relatively durable and long-serving. The contrast between the broadly positive perspectives held by the workforce and a social work literature that often paints a world of professional marginalisation provides a frequent point of challenge to our analysis.